PERUBAHAN STATUS LIFESTYLE KOMSUMTIF PEREMPUAN DALAM MENGGUNAKAN ONLINE SHOP - Sari Utami (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
The lifestyle of the Indonesian people has experienced the development of becoming more modern which is more practical and wants ease in all its activities. This study aims to explain and analyze changes in women's consumptive lifestyles in using online shops. This study uses descriptive qualitative research method, namely research that seeks to describe the object being examined and also dig up as much information as possible about the problem that is the topic of research based on facts that exist in the field, using key informants and informants as data sources. The data presented uses primary data and secondary data through in-depth interviews, field observations, references relating to this research and internet data. Data analysis in this study refers to the interactive analysis model of Matthew B. Miles and A. Michael Huberman. The results of this study that it can be concluded, Women in using online shops that have been active become increasingly consumptive in terms of shopping online to meet needs based on the desire to maintain appearance as a form of self-identity. The women used to buy items such as clothes, hijab, bags, shoes, cosmetics and accessories on an online shop on the basis of supporting the appearance to look beautiful and attractive, fulfilling a more trendy and current lifestyle, then buying the product because of the appearance of judgment that good products or high-priced products will create high self-esteem. They say that products that are purchased online all this time are their main need to maintain their appearance. But in reality unwittingly tends to be excessive and is an elaboration of understanding the theory of consumptive behavior.